Frequency of Anastomosis Leak in Primary Repair in Ileal Perforation - Shah, Muhammad; Iftikhar, Muhammad; Jan, Yousaf; Khan, Shehzad Akbar; Shahzadi, Shimee (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: To determine the frequency of anastomotic leak in primary closure patients presenting with enteric perforation. METHODOLOGY: Through a Descriptive case series Study Design, 253 patients with the perforated ilium and subjected to primary closure were included and followed up post-operatively to determine the anastomosis leak. RESULTS: The mean age of our sample was 42.2 years with a standard deviation of 8.6 years. Out of 253 patients, 70.8% were males, and 29.2% females were. The mean BMI of the study sample was 24.6 + 2.2kg/m2. 61.3% of patients belonged to urban settings, 41.1% were from lower socioeconomic class, and 36.4% had a middle school level education. On follow up, the anastomotic leak was recorded in 18.2% of patients. CONCLUSION: Ileal perforation subjected to primary defect closure is the most performed surgery for treatment, with a significant number of patients developing the anastomosis leak. The frequency of anastomosis leaks is high, and other treatment strategies must be researched to reduce the burden of these complications.